Platelet-Rich Plasma Injections for Advanced Knee Osteoarthritis: A Prospective, Randomized, Double-Blinded Clinical Trial - Joshi Jubert, Nayana (Orthop J Sports Med, 2017)
BACKGROUND: Intra-articular injections of platelet-rich plasma (PRP) to treat symptoms of knee osteoarthritis (OA) have been successfully used in young patients and in the early stages of disease. No previous studies have analyzed outcomes of PRP injections during the late stages. HYPOTHESIS: PRP reduces pain and leads to a more effective and lasting functional recovery than corticosteroid with local anesthetic. STUDY DESIGN: Randomized controlled trial; Level of evidence, 2. METHODS: A total of 75 patients with symptomatic knee OA (Kellgren-Lawrence grade 3 to 4) were enrolled in this study between August 2013 and July 2014. Patients were randomized to treatment either with a single leukocyte-reduced PRP or corticosteroid intra-articular injection. The primary variable was visual analog scale assessment at 1 month. Secondary outcomes were the Knee injury and Osteoarthritis Outcome Score (KOOS) and Short Form–36 (SF-36) at 1, 3, and 6 months after treatment. Patient satisfaction at final follow-up was assessed. Both groups were homogeneous and comparable in baseline characteristics. RESULTS: All variables improved in both groups. Statistical differences between groups were not found for the majority of the outcome variables, although the magnitude of improvements tended to be greater in the PRP group. Quality-of-life differences between values at 3 and 6 months versus baseline increased significantly more in the study group (P = .05 and .03, respectively), and so did general health perception differences at 6 months (P = .018). CONCLUSION: A single PRP intra-articular injection is effective for relieving pain and improving activities of daily living and quality of life in late-stage knee OA. For patients with late-stage knee OA who are 67 years or older, 1 intra-articular injection of PRP has similar results to 1 shot of corticosteroid.